Early Diagnosis of Lymphedema After Breast Cancer Treatment: Bio-Impedance Spectroscopy - Polat, Ayfer Kamali; Karabacak, Ufuk; Mutlu, Vahit; Tomak, Leman; Bilgici, Ayhan (Aves, 2017)
Objective: Breast cancer-related lymphedema is an important health problem. The aim of this study is to ensure early diagnosis of patients at risk of developing lymphedema and revealing the predisposing factors. Materials and Methods: Measurements in the pre-operative period and in postoperative months 3, 6, 9 and 12 and years 2 and 3 were performed prospectively with bio-impedance spectroscopy for patients treated for breast cancer between November, 2013 and November, 2016. Demographic and clinical-pathological data of the patients were investigated to assess the factors that affect the development of lymphedema. Results: 245 measurements were obtained from the 67 patients who participated in the study. 18 (26.8%) patients were diagnosed with lymphedema and 16 (89%) of these patients were clinically diagnosed with stage 0 and 2 (1%) patients with stage 1 lymphedema. The median age was 50.7 (32-77) years. Performing axillary dissection and positivity in more than 3 nodes were found to be statistically significant with a percentage of 63.3% (n=15) and 64.7% (n=11) p=0.049 and p<0.001, respectively. Conclusion: Periodic measurements with bio impedance spectroscopy can be an effective method to diagnose early stage lymphedema after breast cancer, and enable selecting the group of patients who would benefit from early treatment.
Keywords: Lymphedema; Early Diagnosis; Breast Cancer; Bio-Impedance; Spectroscopy